Enfermedades relacionadas con el grupo sanguíneo ABO (2012)
ABSTRACT: The blood group system is the set of antigens encoded by genes that are in one or several locus, which follow a Mendelian behavior. ABO blood group is the most important from the immunohematological point of view, which consists of four blood types: A, B, AB and O. The study of the ABO blood groups is of great importance to determine the hereditary characteristics of each group, blood transfusions, transplants, confirmation of paternity tests and populations studies, among others. Thus, hypotheses have been raised relating to the ABO blood system with several diseases such as malaria, multiple sclerosis, ovarian cancer, and gastric diseases, among others; being the latter aspect the subject to be discussed in this paper. Objective The main objective of this work was to collect information that would identify the diseases related with the ABO blood group, information that could be useful to propose new hypotheses and the formulation of research questions. Materials and methods A literature search was performed using the PubMed, SciELO, Science Direct and Bireme databases with the following descriptors: ABO Blood-Group System, Stomach Neoplasms Gastric Cancer, Peptic Ulcer, Gastritis, Ovarian Diseases, Helicobacter pylori, Von Willebrand Disease, Urinary Infection, Escherichia coli, Malaria, multiple sclerosis, ABO blood group, gastric cancer, ovarian cancer. Results The frequency of blood groups varies between populations, and some of them are universal. These blood groups have been related with various diseases, e.g. the A antigen has been highly related with the development of gastric and ovarian cancer, Helicobacter pylori infection, malaria and multiple sclerosis, while group B with gonorrhea; the group O with the Von Willebrand disease and peptic ulcer, and group AB with venous thrombosis and Dengue. Conclusions The ABO blood group may be an associated factor with the clinical presentation of the pathologies described in this review; however, this association was not clearly stated in any of the studies mainly because they do not have enough evidence to support it. Thus, it is necessary to perform more investigations in order to validate the assumptions underlying these associations.